Komunikowanie o literaturze kryminalnej w Internecie (na podstawie blogu "Żywi i umarli" Mariusza Czubaja) = Detective story in the Internet communication (based on the blog "The Living and the Dead" by Mariusz Czubaj) - Półtorak, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is a contribution to an extensive discussion on the functioning of the literature in Internet communications. The report focuses on the relationship between the sender and the recipient of the message on the example of one form of the internet publication which is blog. It is also an attempt to explain and describe the factors affecting the quality and course of that relationship.
Keywords: komunikacja; internet; blog; nadawca; odbiorca; powieść kryminalna; communication; sender; recipient; crime fiction